The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.17578/19-4-2
|View full text |Cite
|
Sign up to set email alerts
|

Trading Volume and Momentum: The International Evidence

Abstract: We investigate the role of trading volume in predicting the magnitude and persistence of the price momentum phenomenon in markets around the world. Using comprehensive data for 38,273 stocks from 37 countries, we show that past trading volume relates to both the level and persistence of momentum profits. The volume-based early stage momentum strategy outperforms the traditional momentum strategy in 34 out of 37 countries. In addition, we find evidence of a volume effect and we show that the degree of individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…They observed that the momentum effect is absent for the periods characterized by a sentiment of pessimism and appears in optimistic periods. Bornholt et al (2015) found that for the period 1995-2009, the momentum strategy seems to be more profitable in 34 out of 37 developed and emerging countries in case it is based on the past trading volume. The momentum strategy yields on average 0.85 % per month across the countries.…”
Section: Business and Economic Researchmentioning
confidence: 99%
“…They observed that the momentum effect is absent for the periods characterized by a sentiment of pessimism and appears in optimistic periods. Bornholt et al (2015) found that for the period 1995-2009, the momentum strategy seems to be more profitable in 34 out of 37 developed and emerging countries in case it is based on the past trading volume. The momentum strategy yields on average 0.85 % per month across the countries.…”
Section: Business and Economic Researchmentioning
confidence: 99%